Comparison of HAS-BLED with other risk models for predicting the bleeding risk in anticoagulated patients with atrial fibrillation: A PRISMA-compliant article. Issue 25 (19th June 2020) - Zeng, Junquan; Yu, Peng; Cui, Wenjuan; Wang, Xiaoping; Ma, Jianyong; Zeng, Changai
Abstract: Background: The HAS-BLED, HEMORR2 HAGES, ATRIA, and ORBIT scores are used to predict bleeding risk in anticoagulated patients with atrial fibrillation (AF). Recently, these scores have been validated in various studies. Therefore, we aimed to compare the occurrence of major bleeding across different risk categories between HAS-BLED and any of HEMORR2 HAGES, ATRIA, or ORBIT scores. Methods: A systemic literature search of PubMed and Embase databases was conducted to screen the relevant studies. We calculated and pooled the odds ratios (ORs) and 95% confidence intervals (CIs) for a comparative analysis of the occurrence of major bleeding. Results: Nine studies fulfilled the inclusion criteria in this meta-analysis. Compared with HEMORR2 HAGES, there were 87% and 39% reduced rates of major bleeding in the HAS-BLED "low-risk" and "moderate-risk" groups, respectively. Compared with ATRIA, there was an 89% decreased rate of major bleeding in the HAS-BLED "low-risk" group. Compared with ORBIT, there were 84% and 44% reduced rates of major bleeding in the HAS-BLED "low-risk" and "moderate-risk" groups, respectively. Patients with HAS-BLED scores ≥3 showed an approximately 3-fold greater risk of major bleeding compared with patients with scores <3 (OR=3.00, CI: 1.21–7.43). Conclusions: Compared with any of HEMORR2 HAGES, ATRIA, or ORBIT scores, the HAS-BLED score distributed more major bleeding events into the "low" or "moderate" risk categories.